Character Development in Children of Baitul Hidayah Foundation (East Jakarta) - Sujoko Winanto; Abdul Haris Muchtar; Risman Nugraha; Nandito Raditya Rahman; Naufally Dzaki Mahendra; Resti Agustina; Salsabiila; Usamah Al Fatih; Audy Putri Adinda; El Thaariq Is'ad; Alif Zaky Cakramusi Putra; Muhammad Haikal Fuady (SocietalServe: Journal of Community Engagement and Services, 2024)
Character development education for children remains largely overlooked, with the majority only receiving instruction within elementary school classrooms, lacking practical activities to enhance their awareness. In our community empowerment project at the Baitul Hidayah Foundation, we endeavored to address this gap by providing materials, educational sessions, games, and project activities centered around children's character development, employing the 4-color character approach. Our efforts were guided by research focusing on children's character education and its impact on their comprehension of the significance of possessing good character to nurture positive relationships with peers, siblings, and others. Furthermore, following the outcomes of the Focus Group Discussion (FGD) involving the Baitul Hidayah Cijantung Foundation and Group 6 members, it became evident that the Baitul Hidayah Foundation had previously neglected character development education for its students, to the extent of never incorporating it into their curriculum. Therefore, our Community Empowerment Group 4 set out to rectify this deficiency by educating students at the Baitul Hidayah Foundation about the importance of character and providing guidance on its practical application.